Intercostal Artery Perforator Flap for Salvage Breast Reconstruction with Exposed Breast Implants - Felipe Mesa, MD, PhD; Sara Mesa, MD; Federico López, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. Multiple techniques have been described for breast reconstruction surgery after breast implant exposure; breast implant removal and delayed breast reconstruction is the procedure of choice. However, in some mild exposures and infections, we propose an alternative treatment. Methods:. This is a case series of a 14-year study in 16 female patients with mild exposure of a breast implant after breast reconstruction surgery. Salvage surgery was performed on these cases. The defects were between 1 and 6 cm, with a median size of 3.9 × 2.9 cm. Eighteen intercostal artery perforator flaps were used with an island of skin from the inframammary fold; 83.3% were anterior intercostal artery perforator flaps‚ and 16.7% were lateral intercostal artery perforator flaps. Results:. Thirteen of the 16 patients presented infection (81.25%). There was no necrosis of any flap, and the success rate of salvage surgery was 62.5% of all patients. The success of surgery was 53.8% in patients with breast infection and 100% in patients without infection. Seven patients received chemotherapy and radiotherapy, six received only chemotherapy, and nine patients received only radiotherapy. Five of the six patients whose salvage surgery failed were treated with radiotherapy. Conclusion:. This technique can be used as an alternative when there is exposure of the implant‚ even in cases with a mild breast infection and in patients undergoing radiotherapy and chemotherapy.